2018
DOI: 10.1186/s13550-018-0410-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of temporal sampling for 18F-choline uptake quantification in prostate cancer assessment

Abstract: BackgroundSuboptimal temporal sampling of time-activity curves (TAC) from dynamic 18F-fluoromethylcholine (FCH) PET images may introduce bias in quantification of FCH uptake in prostate cancer assessment. We sought to define an optimal temporal sampling protocol for dynamic FCH PET imaging.Seven different time samplings were tested: 5 × 60″, 10 × 30″, 15 × 15″–1 × 75″, 6 × 10″–8 × 30″, 12 × 5″–8 × 30″; 10 × 5″–4 × 10″–3 × 20″–5 × 30″, and 8 × 3″–8 × 12″–6 × 30″. First, the irreversible and reversible one-tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Average K1 value (mL/ccm/min) +/-SD p value only concerns FDOPA but also the quantitative analysis of other PET radiopharmaceuticals [15,[19][20]. We previously demonstrated that a better estimation of 18 F-Choline uptake quantification is obtained using an initial time frame of 5s in prostate cancer assessment using the same PET system [15], shorter than the optimal initial frame of 15 s for FDOPA quantification in glioma assessment in this study. A lower activity concentration of FDOPA in glioma than activity co centration of 18 F-Choline in prostate cancer might be the reason.…”
Section: Time Samplingmentioning
confidence: 66%
See 1 more Smart Citation
“…Average K1 value (mL/ccm/min) +/-SD p value only concerns FDOPA but also the quantitative analysis of other PET radiopharmaceuticals [15,[19][20]. We previously demonstrated that a better estimation of 18 F-Choline uptake quantification is obtained using an initial time frame of 5s in prostate cancer assessment using the same PET system [15], shorter than the optimal initial frame of 15 s for FDOPA quantification in glioma assessment in this study. A lower activity concentration of FDOPA in glioma than activity co centration of 18 F-Choline in prostate cancer might be the reason.…”
Section: Time Samplingmentioning
confidence: 66%
“…Up until now, different time frame samplings were used in publications studying glioma uptake quantification using full kinetic analysis for [5,[12][13][14]. However, we recently showed that a slight difference of temporal sampling induces bias in 18F-Choline uptake quantification in prostate cancer [15]. In this latter study, initial time frame longer than 5 s but also faster than 5 s were not optimal for quantification.…”
Section: Introductionmentioning
confidence: 94%